Principals, partners and pawns: Indonesian civil society organizations and civilian control of the military - Lorenz, Philip (2015)
This dissertation analyzes the extent to which Indonesian CSOs have contributed to the institutionalization of civilian control over the military, one of the most important partial reforms the country had to complete in its transition to democracy after 1999. While international financial support for Civil Society Organizations (CSOs) is an accepted way to promote the deepening and consolidation of democracy, there are few, if any, systematic attempts to evaluate the immediate and tangible contributions civil society organizations have made. Based on a novel integrative theoretical argument the author employs a two-tiered research design that combines in-depth case studies down to the level of individual legal regulations with more concise congruence and process studies of the full sample of legislative projects touching on military reform. The dissertation finds that Indonesian CSOs have made a significant contribution to the institutionalization of civilian control. They managed to limit the political role and institutional autonomy of the military and pushed civilian decision-makers to extend the powers of President and Parliament over its budget and missions. However, CSO success was largely determined by a combination of the institutional interests of civilian decision-makers and the level of veto power and informal counter-pressure the military exerted over decision-makers. Where reform proposals ran counter to civilian institutional interests and met staunch resistance from the armed forces, CSOs were only successful if they could rely on assertive tactics like large-scale demonstration and continuous public pressuring campaigns. Over time, reductions in the level of international funding for CSOs and the proliferation of institutional veto actors on the government side have slowed down the reform process.
Keywords: Hochschulschrift